Benefits of breakfast meals and pattern of consumption on satiety-related sensations in women. (3rd October 2015) - Berti, Cristiana; Riso, Patrizia; Brusamolino, Antonella; Porrini, Marisa
Abstract: This study evaluated the effects on satiety-related sensations of seven isoenergetic cereal-based breakfasts and two fruit products (salad and juice) consumed within breakfast or as a midmorning snack. Nine healthy women participated to 11 sessions following a randomized repeated-measures design. Subjects were asked to consume seven breakfasts consisting of a standard beverage and a different cereal-based product, and also fruit salad or apricot juice consumed within breakfast or as a midmorning snack. Satiety, desire-to-eat and perceived characteristics of products consumed were monitored on Visual Analog Scales from 8:30 am until lunch. Ratings registered and areas under the curve of sensations were analyzed by repeated-measures ANOVA. All breakfast meals maintained the satiety-related sensations at lunch time higher than basal values. The best satiety control was obtained when the fruit salad was consumed as a midmorning snack. Consequently, regular consumption of breakfast and of whole fruit as midmorning snack may be a valid strategy to achieve appetite control.